How Endothelial Cells Adapt Their Metabolism to Form Vessels in Tumors - Zecchin, Annalisa; Kalucka, Joanna; Dubois, Charlotte; Carmeliet, Peter (Frontiers in Immunology, 2017)
Endothelial cells (ECs) line blood vessels, i.e., vital conduits for oxygen and nutrient delivery to distant tissues. While mostly present as quiescent “phalanx” cells throughout adult life, ECs can rapidly switch to a migratory “tip” cell and a proliferative “stalk” cell, and sprout into avascular tissue to form new blood vessels. The angiogenic switch has long been considered to be primarily orchestrated by the activity of angiogenic molecules. However, recent evidence illustrates an instrumental role of cellular metabolism in vessel sprouting, whereby ECs require specific metabolic adaptations to grow. Here, we overview the emerging picture that tip, stalk, and phalanx cells have distinct metabolic signatures and discuss how these signatures can become deregulated in pathological conditions, such as in cancer.